RASIONALITAS PROGRAM TARIA (TABUNGAN HARI RAYA) DALAM MEMBANGUN PENDIDIKAN KARAKTER MASYARAKAT BANJAR ANYAR KAJA KABUPATEN BADUNG - I Wayan Saniarta (JAPAM (Jurnal Pendidikan Agama), 2024)
The phenomenon that appears in Hindu society is that the implementation of Hindu religious ceremonies, on the one hand, tends to be expensive and time-consuming. Every time a ritual is performed, ritual consumption is required both in quantity and quality. Religious activities and rituals, according to Max Weber (1930) and Bourdieu (1977), have an impact on economic and other activities. As a result of this phenomenon, many financial institutions such as banks, LPDs and cooperatives are competing to create holiday savings programs, especially in Bali. The system of practicing holiday savings has been running for quite a long time in Banjar Anyar Kaja, Kerobokan Village. By saving, people can use it for the needs before the holiday. The purpose of this study is to provide character education to the Hindu community regarding the implementation of the Hari Raya Savings program at Banjar Anyar Kaja, Badung Regency. This research is included in qualitative research with a phenomenological approach. The selection of participants in the study was determined using a purposive technique. The data analysis technique used in this study is descriptive, while the data analysis technique is presented in an analytic descriptive form. Implementation of the Hari Raya Savings program in the Banjar Anyar Kaja community, it includes acts of instrumental rationality. The character education values ​​contained in the TARIA program include religious values, self-control, passion, wisdom, not greed, discipline and independence. The implication of community participation in the Hari Raya Savings Program is to provide convenience for the community in preparing finances for welcoming religious holidays. For the community to try to increase enthusiasm in participating in the TARIA program and try to invite family or relatives who have not participated in the program. Keywords: Character Building, Rationality, Saving